Isolation of polyhydroxybutyrate producing bacteria for eco-friendly bioplastic production (Bangladesh Journal of Botany, 2025)
The growing plastic pollution crisis highlights the urgent need for sustainable alternatives such as polyhydroxybutyrate (PHB), a biodegradable polymer. In this study, PHB-producing bacteria were isolated from organic wastes, dumpsite soil, and dairy products. Out of 55 bacterial isolates, five isolates were confirmed as PHB producers.16S rRNA gene sequencing identified them as Bacillus subtilis, Chryseobacterium sp., and Stenotrophomonas spp. PHB was extracted using sodium hypochlorite digestion and characterized by FTIR spectroscopy. Among the isolates, B. subtilis KS-24 and Chryseobacterium sp. KS-25 produced the highest PHB yields (45 mg/ml [41.7% DCW] and 39.75 mg/ml [38.8% DCW], respectively). Optimal production was achieved at 37°C, pH 7, with glucose as the carbon source and ammonium sulfate or peptone as nitrogen sources after 72 hrs incubation. To the best of our knowledge, this is the first report of Chryseobacterium sp. as a PHB producer. These findings highlight promising microbial candidates for industrial-scale bioplastic production, offering an eco-friendly solution to plastic pollution.Bangladesh J. Bot. 54(4): 1053-1059, 2025 (December)